Management Motives and Firm Financial Misstatements in Malaysia - Hussain, Alfiatul Rohmah Mohamed; Sanusi, Zuraidah Mohd; Mahenthiran, Sakthi; Hasnan, Suhaily (International Journal of Economics and Financial Issues, 2016)
This paper discusses issues concerning management motives, which influenced by the situational pressures that lead to the occurrence of financial misstatements. The situational pressures and management motives are measured using financial distress, family ownership, the existence of founder on the firm's board and earnings management of Malaysian public listed firms (referred to as PLCs) that influence the occurrence of financial misstatements. Results show that the existence of founder on the firm's board (FOUNDER) is positively significant while family ownership (FAMOWN) is negatively significant determinants of the occurrence of financial misstatement proxy by financial statement restatements. Two other variables namely financial distress (DISTRESS) and earnings management (EM) interact significantly and positively with financial misstatements. Additionally, FAMOWN positively interacts with EM to affect the occurrence of financial misstatements. Findings reveal that the extent of EM influences financially distressed firms and family-owned firms on the likelihood of financial misstatements by Malaysian PLCs. Keywords: Management motives, financial misstatements, financial statement restatements, Malaysia JEL Classification: G3